2011
DOI: 10.1007/s11596-011-0673-z
|View full text |Cite
|
Sign up to set email alerts
|

Re-expression of cell adhesion molecule inhibits growth and induces apoptosis of human pancreatic cancer cell line PANC-1

Abstract: This study examined the expression of cell adhesion molecule 1 (CADM1) in pancreatic cancer and the possible mechanism. The expression of CADM1 was detected by immunohistochemistry in tissues of pancreatic cancer, pancreatitis, and normal pancreas. The plasmid pcDNA3.1-Hygro(+)/CADM1 was transfected into PANC-1 cells (a pancreatic cancer cell line). The expression of CADM1 in the transfected cells was determined by RT-PCR and Western blotting. Cell growth was measured by the MTT method and cell apoptosis by fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Our data show for the first time a linkage between HPV16 positivity and CADM1 methylation in OPSCC. CADM1 plays a role in cell–cell adhesion and reduced expression of this gene is correlated with lymph node metastasis . Interestingly, CADM1 was also often methylated in cervical cancer (Fig.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our data show for the first time a linkage between HPV16 positivity and CADM1 methylation in OPSCC. CADM1 plays a role in cell–cell adhesion and reduced expression of this gene is correlated with lymph node metastasis . Interestingly, CADM1 was also often methylated in cervical cancer (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…CADM1 plays a role in cell-cell adhesion and reduced expression of this gene is correlated with lymph node metastasis [46]. Interestingly, CADM1 was also often methylated in cervical cancer (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Our finding demonstrated that CADM1 was a target gene of miR-196b in PANC-1 cells. CADM1, which is also called as TSCL1, has been reported to be involved in cell adhesion, migration, and apoptosis 22 – 24 . Besides, previous study has found that CADM1 expression was down-regulated in different types of cancers, including gastric cancer, breast cancer, and lung carcinoma 25 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Loss of heterozygosity for the CADM1 gene and methylation of the CADM1 promoter is shown to promote PC progression, with CADM1 promoter hypermethylation detected in nonsmall cell lung cancer, pancreatic, hepatocellular, and prostate cancers. 64,67,[73][74][75]…”
Section: Cell Adhesion Moleculementioning
confidence: 99%
“…Cell adhesion molecule 1 was also reported to suppress PDAC metastasis by inducing cell cycle arrest at the G 1 phase and promoting cellular apoptosis. Loss of heterozygosity for the CADM1 gene and methylation of the CADM1 promoter is shown to promote PC progression, with CADM1 promoter hypermethylation detected in nonsmall cell lung cancer, pancreatic, hepatocellular, and prostate cancers 64,67,73–75 …”
Section: Cell Adhesion Moleculementioning
confidence: 99%